Implementation Of Restorative Justice In Traffic Accident Settlement - Indra Jaya Syafputra; Maryanto Maryanto; Jawade Hafidz (Universitas Islam Sultan Agung, 2021)
This study aims to determine and analyze the implementation of restorative justice in resolving traffic accident cases in the jurisdiction of the Rembang Police and the obstacles that arise in the implementation of restorative justice in resolving traffic accident cases in the jurisdiction of the Rembang Police and their solutions. The approach method used is sociological juridical, descriptive analytical research specifications, types and sources of data using primary and secondary data, data collection methods are field studies and literature studies, while the data analysis method uses qualitative analysis. The results of the study indicate that the implementation of restorative justice in resolving traffic accident cases in the jurisdiction of the Rembang Police is aimed at justice by referring to the Criminal Procedure Code, the LLAJ Law, the Police Law, and the National Police Perkap Number 6 of 2019. In its application there are obstacles, namely the lack of legal awareness of community and intervention from third parties.